Technological aspects of probiotics obtaining - Starovoitova, Svitlana; Skrotska, Oksana (My University, 2014)
Сurrent groups of drugs using for correction of the humans normal microflora were reviewed. The types of problems and promising directions for improving probiotics were shown. Different probiotic's drug-forms were considered, and the possible aspects of the efficiency of bacterial agents were shown. Technological methods to improve technologies of obtaining and extending the shelf life of probiotic were analyzed. The technology of polystrain substance of probiotic with high therapeutic properties and spread spectrum of therapeutic action were shown
Keywords: technology; multyprobiotic; probiotic microorganisms; технологія; мультипробіотик; пробіотичні мікроорганізми; технология; мультипробиотик; пробиотические микроорганизмы; кафедра біотехнології і мікробіології